2014
DOI: 10.1002/hep.26982
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A and its analogs inhibit hepatitis B virus entry into cultured hepatocytes through targeting a membrane transporter, sodium taurocholate cotransporting polypeptide (NTCP)

Abstract: Chronic hepatitis B virus (HBV) infection is a major public health problem worldwide. Although nucleos(t)ide analogs inhibiting viral reverse transcriptase are clinically available as anti-HBV agents, emergence of drug-resistant viruses highlights the need for new anti-HBV agents interfering with other targets. Here we report that cyclosporin A (CsA) can inhibit HBV entry into cultured hepatocytes. The anti-HBV effect of CsA was independent of binding to cyclophilin and calcineurin. Rather, blockade of HBV inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
248
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(255 citation statements)
references
References 48 publications
5
248
2
Order By: Relevance
“…Recent studies showed that cyclosporin A and its derivatives, neutralizing antibody against HBV surface protein, and compounds known to inhibit the NTCP transporter activity could inhibit HBV entry using NTCP through interfering with the binding between NTCP and the pre-S1 domain of the HBV large envelope protein (Iwamoto et al, 2014;Nkongolo et al, 2013;Watashi et al, 2013), thus, proposing a novel strategy to identify anti-HBV agents by targeting NTCP. Whether NTCP polymorphisms, including the rs2296651 polymorphism, are relevant to the action of anti-HBV agents targeting NTCP may be a focus of future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that cyclosporin A and its derivatives, neutralizing antibody against HBV surface protein, and compounds known to inhibit the NTCP transporter activity could inhibit HBV entry using NTCP through interfering with the binding between NTCP and the pre-S1 domain of the HBV large envelope protein (Iwamoto et al, 2014;Nkongolo et al, 2013;Watashi et al, 2013), thus, proposing a novel strategy to identify anti-HBV agents by targeting NTCP. Whether NTCP polymorphisms, including the rs2296651 polymorphism, are relevant to the action of anti-HBV agents targeting NTCP may be a focus of future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Iwamoto et al [120] , Watashi et al [121] and Tsukuda et al [122] reported that cyclosporine A and its analogs blocked HBV entry through inhibiting the interaction between NTCP and the HBV large surface protein. HBV entry inhibitors might also be useful for controlling HBV infection in the near future.…”
Section: Sodium Taurocholate Cotransporting Polypeptidementioning
confidence: 99%
“…The other possibility is that after binding of HBV envelope protein with NTCP, the receptor is internalized by endocytosis allowing virus to enter the hepatocyte [72,73]. If virus enters the cells through endocytosis then what would be the signal for internalization and how is that signal generated?…”
Section: Sodium Taurocholate Cotransporting Polypeptide (Ntcp)mentioning
confidence: 99%
“…These includes Myrcludex-B [43], Cyclosporin A (CsA), progesterone, propranolol and bosentan [73]. NTCP substrates, such as taurocholate, tauroursodeoxycholate and bromosulfophthalein, also inhibited HBV infection [43,49,73].…”
Section: Sodium Taurocholate Cotransporting Polypeptide (Ntcp)mentioning
confidence: 99%